PENERAPAN COOPERATIVE LEARNING TIPE PICTURE AND PICTURE DALAM MENINGKATKAN MINAT BELAJAR DI SMPN 47 MAKASSAR - Nugraha, Muhammad Agung; Syahid, Akhmad; Surani; Nurlaelah; Darmawangsa, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a Classroom Action Research (CAR) aimed at improving students’ learning interest through the implementation of the Picture and Picture learning model in Islamic Education for class VIII.6 at SMP Negeri 47 Makassar. The research subjects consisted of 27 students. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation sheets, learning interest questionnaires, evaluation tests, and documentation. The indicators of learning interest observed included enjoyment, attention, interest, and student involvement. The results showed that the implementation of the Picture and Picture learning model effectively increased students’ learning interest progressively. In the pre-cycle stage, learning mastery reached 32.26%, increased to 54.84% in Cycle I, and showed a significant improvement in Cycle II to 87.10%. Additionally, improvements were observed across all aspects of learning interest, as indicated by students’ increased enthusiasm, focus, participation, and active engagement in the learning process. Therefore, it can be concluded that the Picture and Picture learning model is effective in enhancing students’ learning interest in Islamic Education.